Current trends in the development of engines for unmanned aerial vehicle - Anatolii Savchenko; Dmytro Obodets (Авіаційно-космічна техніка та технологія)
The subject of this study is the current state and prospects for the development of the market for unmanned aerial vehicles (UAVs) and power plants. The purpose of this work was to identify trends in the development of UAV engines of various classes. Task: collection, systematization, and analysis of information on the most common engines of reconnaissance and strike UAVs of the operational-tactical level, as well as UAVs of the "barrage ammunition" class. This article provides a brief description of various types of UAV power plants, and their main advantages and disadvantages are given, which are often decisive when choosing the type of power plant for a specific UAV. It was found that a power plant with an internal combustion engine (ICE) is best suited for use in medium- and long-range UAVs.This study demonstrated that four-stroke internal combustion engines are most commonly used in reconnaissance-strike UAVs at both operational and tactical levels. The features of the design and characteristics of four-stroke internal combustion engines, which have become the most widely used UAVs, are described. It was determined that the introduction of turbocharging or increasing the pressure is the main means of forcing four-stroke internal combustion engines, which makes it possible to simultaneously achieve high specific power and high brake efficiency of the engine over a wide range of altitudes during its operation. It is shown that one of the most important tasks for a long-range UAV engine is to reduce the specific brake fuel consumption. Thus, there is a tendency to promote the use of high-powered aviation diesels in long-range UAVs. It was determined that the main requirements for UAV engines of the "barrage ammunition" class are high specific power, low cost and adaptability to mass production. This study shows that gasoline two-stroke internal combustion engines with crank-chamber scavenging are extremely widespread in UAVs of the "barrage ammunition" class. The design features and characteristics of UAV two-stroke internal combustion engines are described. The main means of ensuring high specific power of such two-stroke internal combustion engines are increasing the engine RPM, optimizing gas exchange processes, and reducing the weight of the construction by using new materials. Conclusion. The results show that depending on the UAV type, the set of engine requirements can vary significantly. Modern trends in the development of UAV engines of various classes have been determined. Potentially promising directions for increasing the efficiency of engines and for comprehensive improvement of their indicators and characteristics have been determined.